Inventory of Potential Weeds Under Stands of Immature Nutmeg Plants in Allang Country, West Leihitu District Central Maluku Regency - Vilma Laurien Tanasale; Nureny Goo (Faculty of Agriculture, Pattimura University, 2023)
Weeds are plants whose presence is undesirable because it can reduce production. The composition and diversity of weeds also determines the structure of the planting area which will ultimately affect the ecological function. The presence of weeds can be found in all planting areas. This research was carried out in Negeri Allang, Central Maluku Regency in March 2022. This research aimed to inventory the types of weeds under nutmeg plantations. The data collection process in the field was carried out using the quadratic method with sample plots measuring 1 m x 1 m and placed under immature nutmeg plantations. Observation of weeds was carried out destructively, namely the types of weeds in the sample plots were removed to calculate the individual and the biomass of each type.The results of the study found 16 types of weeds in the nutmeg planting area of immature stages. Commelina diffusa (Burm). F. weed type SDR 17.79%. is the dominant weed in the nutmeg plantation area of immature stages.